2012
DOI: 10.1121/1.3682043
|View full text |Cite
|
Sign up to set email alerts
|

Time–frequency analysis of linear and nonlinear otoacoustic emissions and removal of a short-latency stimulus artifact

Abstract: Click-evoked otoacoustic emissions (CEOAEs) are commonly recorded as average responses to a repetitive click stimulus. If the click train has constant polarity, a linear average results; if it contains a sequence of clicks of differing polarity and amplitude, a nonlinear average can be calculated. The purpose of this study was to record both protocols from the same set of ears and characterize the differences between them. The major features of CEOAEs were similar under both protocols with the exception of a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
(60 reference statements)
2
17
0
Order By: Relevance
“…Additionally, it was shown that when the method of artifact reduction was applied to the linear mode TEOAE recordings, the time-frequency properties of the data were similar to the responses elicited by the non-linear protocol. The TEOAE latency-frequency dependence for newborn ears studied here was found to have similar characteristics to those of adults [7] . In terms of latency-frequency properties, there seemed to be no maturational effects [21] , which are found with response level [22] .…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Additionally, it was shown that when the method of artifact reduction was applied to the linear mode TEOAE recordings, the time-frequency properties of the data were similar to the responses elicited by the non-linear protocol. The TEOAE latency-frequency dependence for newborn ears studied here was found to have similar characteristics to those of adults [7] . In terms of latency-frequency properties, there seemed to be no maturational effects [21] , which are found with response level [22] .…”
Section: Discussionsupporting
confidence: 49%
“…Only the range 0-5 ms in time and 0-2200 Hz in frequency was windowed and filtered, while for frequencies above 2200 Hz, only the initial 2.5 ms were windowed. The effect of this change was preservation of the high frequency response when using the linear protocol [7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, participants with an excessive number of SOAEs, greater than five, were excluded since it may impact the CEOAE levels. This criterion was set based on the mean incidence of SOAEs consolidated from several studies (Jedrzejczak et al, 2008;Penner and Zhang, 1997;Strickland et al, 1985;Talmadge et al, 1993). This condition was strict because CEOAEs recorded by the linear recording technique are less influenced by synchronous SOAEs (Jedrzejczak et al, 2012).…”
Section: Measurement Quality Controlmentioning
confidence: 99%